Effect of Emotional Intelligence on Transformational Leadership at Management Level in PT Tunas Baru Lampung TBK-Banyuasin - Mersi Putri Ayu; Dina Mellita (Budapest International Research and Critics University, 2022)
This study aims to determine and analyze the influence of Emotional Intelligence on Transformational Leadership at Management Level at PT. Tunas Baru Lampung, Tbk-Banyuasin. The research method that the author uses in this study is a quantitative research method with a descriptive approach with an emphasis on theory testing through the measurement of research variables through the distribution of research questionnaires. The population in this study amounted to 70 employees at the management level at PT. Tunas Baru Lampung, Tbk-Banyuasin. The sampling technique used in this study is probability sampling with the technique taken is Simple Random Sampling. The analytical technique used in this research is simple linear regression using SPSS version 25 software.